A Bourdieusian perspective in exploring the emergence and evolution of the field of Islamic microfinance in Indonesia. Issue 4 (9th July 2018) - Handayani, Wuri; Haniffa, Roszaini; Hudaib, Mohammad
Abstract : Purpose: Microfinance institutions (MFIs), including Islamic microfinance institutions (IMFIs) in Muslim countries, have spread across the globe and transformed into a new industry. However, how IMFIs in Indonesia evolved to become an important sector serving society has not been rigorously explored. Therefore, the purpose of this paper is to address the lacuna on the emergence of an industry by examining the development of Islamic microfinance sector in Indonesia. Design/methodology/approach: The paper adopts the historical research method to narrate the evolution of this specific sector based on the data collected through oral history and published academic research documents during various periods of Indonesia's economic and political milieu. Findings: This paper demonstrates that the emergence and development of IMFIs in Indonesia has been shaped within the wider process of socio-political changes, particularly, the role of Islamic movement and politics in Indonesia. Originality/value: Most studies investigating the emergence and transformation of institution or industry adopt the static approach, which has been criticised as it fails to consider the process of emergence, growth path and the survival of organisations. Hence, this paper contributes to the literature by analysing the institutional evolution by locating the institution inside its wider environmental context by using Bourdieu's concept of field to narrate the historical development of IMFIs from its emergence and evolution to become a significant new industry in the country.